Adiponectin correlates in Malaysians: a comparison of metabolic syndrome and healthy respondents - Md Aris, Mohd Aznan; Khattak, Muhammad Muzaffar Ali Khan; Abdullah, Nor Zamzila; Mohd Rus, Razman; Draman, Samsul (Science and Education Publishing, 2014)
Several studies have demonstrated that adiponectin has strong association with metabolic syndrome and its factors like obesity, insulin resistance, type 2 diabetes, dyslipidemia and coronary artery disease. A total 152 subjects were registered in this study. Among the respondents 76 were with metabolic syndrome (based on the criteria of the International Diabetes Federation (IDF) world-wide definition) and another 76 matching healthy respondents. The factors which were studied for possible differences and association include central obesity (body mass index (BMI) & waist circumference (WC), hypertension (systolic blood pressure (SBP), diastolic blood pressure (DBP), dyslipidemia (total cholesterol (Tc), high density lipoprotein Cholesterol (HDL-c), low density lipoprotein Cholesterol (LDL-c), Triglyceride (TG) and Adiponectin (AD), fasting plasma glucose and history of smoking. The data collected was statistically analyzed using SPSS statistical software version 12.0. Two tests were performed including paired t-test and Pearson correlation analysis. The collected data revealed some interesting differences for the healthy and metabolic syndrome respondents. There were significant (P<0.01) differences for central obesity and hypertension. There were also significant (P<0.01, P<0.1, P<0.01) differences for TG, HDL and fasting plasma glucose. More importantly, AD concentration was significantly (P<0.05) higher in normal healthy respondents. The AD showed strong negative association (r = - 2.91, P<0.001) with FBG and positive association (r = 2.89, P<0.001) with HDL-c. The present study provides baseline information on the predication of metabolic syndrome in Malaysian population.